Cloning, Functional Characterization and Site-Directed Mutagenesis of 4-Coumarate: Coenzyme A Ligase (4CL) Involved in Coumarin Biosynthesis in Peucedanum praeruptorum Dunn - Liu, Tingting; Yao, Ruolan; Zhao, Yucheng; Xu, Sheng; Huang, Chuanlong; Luo, Jun; Kong, Lingyi (Frontiers in Plant Science, 2017)
Abstract Coumarins are the main bioactive compounds in Peucedanum praeruptorum Dunn, a common Chinese herbal medicine. Nevertheless, the genes involved in the biosynthesis of core structure of coumarin in P. praeruptorum have not been identified yet. 4-Coumarate: CoA ligase (4CL) catalyzes the formation of hydroxycinnamates CoA esters, and plays an essential role at the divergence point from general phenylpropanoid metabolism to major branch pathway of coumarin. Here, three novel putative 4CL genes (Pp4CL1, Pp4CL7, and Pp4CL10) were isolated from P. praeruptorum. Biochemical characterization of the recombinant proteins revealed that Pp4CL1 utilized p-coumaric and ferulic acids as its two main substrates for coumarin biosynthesis in P. praeruptorum. Furthermore, Pp4CL1 also exhibited activity towards caffeic, cinnamic, isoferulic, and o-coumaric acids and represented a bona fide 4CL. Pp4CL7 and Pp4CL10 had no catalytic activity towards hydroxycinnamic acid compounds. But they had close phylogenetic relationship to true 4CLs and were defined as 4CL-like genes. Among all putative 4CLs, Pp4CL1 was the most highly expressed gene in roots, and its expression level was significantly up-regulated in mature roots compared with seedlings. Subcellular localization studies showed that Pp4CL1 and Pp4CL10 proteins were localized in the cytosol. In addition, site-directed mutagenesis of Pp4CL1 demonstrated that amino acids of Tyr-239, Ala-243, Met-306, Ala-309, Gly-334, Lys-441, Gln-446 and Lys-526 were essential for substrate binding or catalytic activities. The characterization and site-directed mutagenesis studies of Pp4CL1 lays a solid foundation for elucidating the biosynthetic mechanisms of coumarins in P. praeruptorum and provides further insights in understanding the structure-function relationships of this important family of proteins.